ANALISIS ASAM AMINO PENSTIMULASI SEKRESI INSULIN DALAM BIJI KECIPIR, BIJI ASAM, DAN BIJI KELOR DENGAN HPLC - Rizkiyanti, Dita; Suaniti, Ni Made; Ratnayani, Ketut (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016, 2016)
Seeds are a source of high protein when compared with other parts of the plant. Compared to soy bean, the use of winged bean seeds, tamarind seeds, moringa seeds as protein sources are still very limited. Protein composed of several amino acids bond together to form a polypeptide. Some amino acids have been investigated to act as stimulating insulin secretion, namely, arginine, alanine, phenylalanine, isoleucine, and lysine. The aim of this study was to determine the potential content of amino acids stimulating the secretion of insulin in winged bean seeds, tamarind seeds, and moringa seeds. Based on the total content of amino acids in each seeds, the results showed that moringa seeds have the highest levels of total amino acids stimulating insulin secretion (16.4%), followed by winged bean seeds (16.2%), and tamarind seeds (12.1%). But if seen by the levels of each amino acid, the winged bean seeds on average had the highest amino acid content. The highest levels of arginine, alanine, phenylalanine, isoleucine, and leucine were found in winged bean seeds, while only one specific amino acid i.e. lysine was found to be the highest level on moringa seeds. It can be concluded that the most potential seeds as a source of amino acids stimulating insulin was the winged bean seeds, that will be useful in the prevention or treatment of diabetes mellitus.
Keywords: amino acid, stimulating insulin secretion, winged bean seeds, tamarind seeds, moringa seeds